Pengaruh Model Pembelajaran Project Based Learning Berbantuan Training Kit Bardi Smart Home Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Instalasi Penerangan Listrik Kelas XII Titl Di Sekolah SMK Negeri 1 Pungging - Makhruz Maulana Putra; Tri Rijanto (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
In the learning process, of course there is a need for a learning model that can support student learning activities in class. Project based learning model (PjBL) is suitable to be applied in vocational high schools, because it actively involves students in the learning process and can support student skills. This research aims to: (1) Find out the effect of the PjBL model assisted by the Bardi smart home training kit on student knowledge learning outcomes; (2) Knowing the effect of the PjBL model assisted by the Bardi Smart Home training kit on student skills learning outcomes; (3) Knowing the effect of the PjBL model assisted by the Bardi smart home training kit on student attitude learning outcomes. The research was conducted on the Electrical Lighting Installation subject class XII TITL Vocational High School 1 Pungging. The research method used is quasi-experimental with nonequivalent control group design. The sample of this research were students in class XII TITL 1 as the control class and class XII TITL 2 as the experimental class. Data analysis techniques use Independent T-Test for normal data and the Mann Whitney non-parametric test for abnormal data. The research results show that: (1) There is an effect of the PjBL model assisted by the Bardi smart home training kit on student knowledge learning outcomes with a significance value of 0.000; (2) There is an effect of the PjBL model assisted by the Bardi smart home training kit on student skills learning outcomes with a significance value of 0.000; (3) There is an effect of the PjBL model assisted by the Bardi smart home training kit on student attitude learning outcomes with a significance value of 0.005.